2005
DOI: 10.1021/bi051624q
|View full text |Cite
|
Sign up to set email alerts
|

Sumoylation of the Yeast Gcn5 Protein

Abstract: Sumoylation, the process by which the ubiquitin-related SUMO protein is covalently attached to lysine side chains in other proteins, is involved in numerous processes in the eukaryotic cell, including transcriptional repression. In this study, we identify Gcn5, the histone-modifying subunit of the transcriptional regulatory complex SAGA, as a sumoylation substrate in yeast. In vitro, multiple sumoylation of recombinant Gcn5 alone or as a trimer with its interacting proteins Ada2 and Ada3 did not affect Gcn5's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Proteomics studies in the latter two organisms showed that the SAGA complex is also sumoylated at various subunits (Golebiowski et al, 2009; Makhnevych et al, 2009). In yeast, Gcn5 sumoylation appears to inhibit SAGA-mediated gene expression (Sterner et al, 2006), which agrees with the notion that sumoylation generally causes gene repression. In Arabidopsis, GCN5 is associated with about one third of 20,000 promoter regions analyzed (Benhamed et al, 2008).…”
Section: Sumoylation Of Conserved Subunits Of Chromatin-modifying Prosupporting
confidence: 59%
“…Proteomics studies in the latter two organisms showed that the SAGA complex is also sumoylated at various subunits (Golebiowski et al, 2009; Makhnevych et al, 2009). In yeast, Gcn5 sumoylation appears to inhibit SAGA-mediated gene expression (Sterner et al, 2006), which agrees with the notion that sumoylation generally causes gene repression. In Arabidopsis, GCN5 is associated with about one third of 20,000 promoter regions analyzed (Benhamed et al, 2008).…”
Section: Sumoylation Of Conserved Subunits Of Chromatin-modifying Prosupporting
confidence: 59%
“…In cells, Siz1 has been reported to be present at only ~150 molecules/cell (Ghaemmaghami et al, 2003). This model might also account for the observation that often many subunits of a particular multisubunit complex are modified by SUMO (Denison et al, 2004;Hannich et al, 2005;Panse et al, 2004;Sterner et al, 2006;Wohlschlegel et al, 2004). Binding of a Siz protein to a complex might target multiple subunits for sumoylation simultaneously.…”
Section: Discussionmentioning
confidence: 98%
“…AllR mutant proteins, in which all lysines have mutated into arginines, have been used to reveal the functional relevance of SUMO modification in target proteins. Smt3 also has been successfully fused to the N-or C-terminus of target proteins to mimic constitutive sumoylation in vivo [55,56]. These fusion constructs lacked the C-terminal Gly-Gly residues of SUMO (i.e., the natural cleavage site), so that the SUMO structure formed but was not cleaved by endogenous SUMO proteases in yeast.…”
Section: Sumoylation Of Target Proteinsmentioning
confidence: 99%